Investmentempfehlungen in deutschen Börsenmagazinen. : Eine pragmatisch leser(un)freundliche Textsorte - Puato, Daniela (Linguistik Online, 2023)
The topic of this study is the pragmatics of investment recommendations in German financial magazines. The target reader, mainly a private investor, expects a clear assessment of the quality of the investment product and a corresponding operative instruction regarding his investment decision (whether he should buy, sell or hold a certain stock, mutual fund, or bond). On the basis of a large corpus of over five thousand texts from the most important weekly magazines (Börse Online, Der Aktionär, Focus Money) it is investigated to what extent this text genre meets reader expectations. Investment recommendations show a potentially complex pragmatic structure including, among others, a headline, an evaluation of relevant arguments (pros and cons) and the operative instruction (buy/sell/hold). However, crucial elements may be missing or even give conflicting hints concerning the investment decision. Moreover, operative instructions often tend to be formulated as rather vague indirect speech acts, limiting the overall pragmatic user-friendliness. These apparent inconsistencies can be put down to a secondary pragmatic goal from the perspective of the writer: not only to give good advice, but also not to be held accountable for bad advice.